Safety and efficacy of early oral feeding for enhanced recovery following gastrectomy for gastric cancer: A systematic review. (March 2019) - Tweed, Thaís; van Eijden, Yara; Tegels, Juul; Brenkman, Hylke; Ruurda, Jelle; van Hillegersberg, Richard; Sosef, Meindert; Stoot, Jan
Abstract: Background: Early oral feeding (EOF) is believed to be a crucial item of Enhanced Recovery After Surgery (ERAS) programs. Though this is widely accepted for colorectal surgery, evidence for early oral feeding after gastrectomy is scarce. The aim of this review is to assess the evidence of safety and benefits of early oral feeding after gastrectomy in patients with gastric cancer. Methods: A systematic literature search of Pubmed, Embase and Cochrane was performed for eligible studies published till September 2018. Studies were analyzed and selected by predetermined criteria. Results: After having assessed 23 eligible articles, a total of four randomized controlled trials (RCT) remained who fully met all requirements to be included in this review. All four RCTs compared early oral feeding (n = 320) with conventional care (n = 334) after gastrectomy. In all four studies, EOF was associated with a decreased length of hospital stay ranging from −1.3 to −2.5 days when compared to conventional care. A faster time to first flatus was recorded in all four studies in the EOF group, ranging from −6.5 hours to −1.5 days. Furthermore, EOF does not increase postoperative complication risk when compared to conventional care. Conclusion: Current evidence for early oral feeding after gastrectomy is promising, proving its safety, feasibility and benefits. However, most studies have been conducted amongst an Asian population. Well powered and larger randomized controlled trials performed amongst a Western population is needed. Highlights: Early oral feeding promotes enhanced recovery after stomach surgery. Studies show it is safe, feasible & beneficial after surgery for stomach cancer. Earlier food intake does not increase complication risk after stomach surgery. Early oral feeding leads to faster recovery and a shorter hospital stay.